Formulation and dissolution assessment of a novel repeat action tablet containing a decongestant and an antihistamine - Verner, Jennifer Joan (Rhodes University, Faculty of Pharmacy, Pharmacy, 2001)
Controlled and sustained release dosage forms are the focus of worldwide research. These dosage forms facilitate patient compliance by simplifying the dosage regimen, and decrease the risk of adverse effects by reducing large fluctuations in the plasma concentration of the drug. The objective of this study was to formulate a repeat-action tablet to provide a sustained release dose of pseudoephedrine sulfate (PSS), and an immediate release dose of both PSS and loratadine. The release profile was compared to that of a commercially available preparation, Clarityne-D®. This formulation developed presents a novel mechanism of sustaining the release of PSS. The prototype tablet consisted of a sustained release core coated with an ethylcellulose dispersion to introduce a lag phase into the release profile and a second outer film coat incorporating PSS and loratadine. The core comprised an ethylcellulose granulation of PSS compressed into a hydroxypropyl methylcellulose matrix. The release of PSS from prototypes was assessed using USP Apparatus 3, as this apparatus was more representative of in vivo conditions and discriminated more effectively between the different tablet compositions produced during development. All dissolution samples were analysed for PSS and loratadine using validated highperformance liquid chromatographic methods. The prototype sustained release cores were found to be more resistant than the reference product to elevated temperature and humidity (40°C/87% RH) with fewer observed changes to the release profiles following storage for up to six months. This study was a feasibility study to obtain proof of concept. The release profile obtained from the prototype tablets was similar (f₂ = 50.0) to that of the reference product. Further development and optimisation of this dosage form is necessary, including evaluation of the choice of hydrophobic polymer, the effect of compression force and tablet geometry and characterisation of the release mechanism from the coated matrix. Assessment of these factors is necessary in order to optimise the formulation with respect to the desired therapeutic objectives.
Keywords: Antihistamines; Tablets (Medicine); Tableting; Ephedrine